Green finance from the perspective of Islamic social finance: A case study of microfinance practices in Istanbul - Hendra, Testru; Mustion, Seppi; Nasution, Karimaturrizky Syukri; Handra, Rana Nurulita (Center for Islamic Economics and Development Studies [P3EI], 2025)
Purpose – This study aims to explore and analyze the integration of green finance principles with Islamic microfinance practices in Istanbul, Turkey. Specifically, it examines how Islamic microfinance institutions incorporate environmental and social sustainability values into their operational activities and investigates the role of Islamic social finance instruments, such as zakat, infak, sedekah, waqf, and qard al-hasan, in supporting the achievement of the Sustainable Development Goals (SDGs).Methodology – Employing a qualitative research design with a case study approach, data were collected through in-depth interviews, participatory observations, and document analysis involving key stakeholders of Islamic microfinance institutions in Istanbul. The data were analyzed using thematic analysis to uncover recurring patterns and themes related to the adoption of green finance principles. The key variables examined included environmental sustainability, social sustainability, Sharia compliance, and the effectiveness of Islamic social finance tools.Findings – Findings indicate a positive but partial integration of green finance principles into Islamic microfinance practices, with notable contributions from zakat and waqf in promoting social welfare and environmental responsibility. However, challenges such as regulatory constraints, limited awareness, and difficulties in measuring impact have also been identified.Implications – These implications underscore the need for enhanced regulatory support, capacity building, and awareness programs to foster a more robust and sustainable Islamic microfinance sector.Originality – This study contributes both conceptually and practically to the literature on sustainable Islamic finance and provides strategic recommendations for policymakers, practitioners, and researchers. This study is expected to support the advancement of inclusive, ethical, and environmentally responsible microfinance models aligned with Sharia principles and global sustainability agendas.